KEGIATAN SISWA DI LUAR SEKOLAH PADA JAM PELAJARAN SEKOLAH ( STUDI : SISWA SEKOLAH MENENGAH ATAS ) - Ayu Kartika Purba; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Delinquency of students is a student form of behavior that deviates from school rules.Delinquency of students many kinds, one of them is ditching. Skipping is a behavior thatviolates social norms as a result of Kartono's poor environmental conditioning process(2013). Misdemeanor mischievous occurs among high school students (SMA). Oftenencountered students who ditch from school gathered in oil palm plantations, gathered installs or playstation play. As the school students gather in the oil palm plantations they dosmoke, play mobile phones. This study aims to find out what activities students do whenditching the school and what the reason students do skip school at the school time. The theoryused in this research is Theory of Deviation, Theory of Behavior Deviation (DevianBehavior) according to Paul B.Harton (Elly M.Setiadi, 2011). This research uses Qualitativemethod. Data analysis is done by qualitative descriptive method, the data retrieval techniquein this research is accidental where the number of respondents are 6 students of Senior HighSchool. To collect research data using observation method, documentation and interview.From the results of the study, it can be concluded that the students' activities during schoolwork are often gathered in the oil palm plantations for smoking, playing mobile. and thereason students do skip school because students feel bored while in school and bored whilestudying.Keywords: Students, ditching, truant activities